Globalization and technology: theoretical foundations of lexical-semantic changes in English - Esirgapov , Muhiddin (The Lingua Spectrum, 2025)
This paper explores the theoretical underpinnings of lexical-semantic changes in the English language in the context of globalization and technological advancement. With English serving as a dominant global language, its vocabulary has undergone profound shifts influenced by digital innovation, cross-cultural exchange, and evolving modes of communication. The research illustrates corpus analysis, semantic theory, and sociolinguistic approaches to investigate how new terms emerge, how existing words shift in meaning, and how global and local dynamics impact on linguistic trends. Case studies of words such as “fintech”, “metaverse”, “ping”, and “drone” illustrate how technological contexts reform semantics. The study also emphasise the role of social media, generational language trends, and the tension between linguistic globalization and local identity preservation. Eventually, the researches underscore the adaptability of English and its capacity to reflect and respond to the ever-changing realities of modern life. This research provide with a deeper understanding of how language not only evolves but also mediates the interface between culture, technology, and communication in a globalized era.